System of measurement and registration of signals of biologically — active points for acupuncture therapies - Azarov, O. D.; Halahan, O. Ya.; Zvenyhorodskyi, E. L.; Snihur, A. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The system of measurement and registration of signals of biologically — active points for acupuncture therapies is synthesized on the basis of definition of real characteristics of signals of such points. It is shown, that this system allows to expand functionalities of existing systems of diagnostics in the area of acupuncture therapies.